ASSESSMENT OF THE PHYSICAL DEVELOPMENT OF SCHOOL CHILDREN ASSOCIATED WITH HELMINTHIASIS DISEASES - Aida Sh. Kamilova; Djamshid Y. Kamilov (Central Asian Journal of Medicine, 2024)
Intestinal helminthosis is common among children. Ear infections are rare, but they can be reduced in studies, physical fitness, cognitive functions, shuningdeck, school and academic courses. In addition, he seeks to expand educational research opportunities, find a higher education institution and advance his career. In childhood, intensive growth and intensive metabolic processes occur, which determine the high need of the child's body for vitamins and minerals. Children affected by vomiting are associated with eating the course of the disease, and especially in children, there is a decrease in height, low weight and anemia.